2021
DOI: 10.1111/1467-9566.13273
|View full text |Cite
|
Sign up to set email alerts
|

Women’s empowerment and their experience to food security in rural Bangladesh

Abstract: Global discourses have advocated women's empowerment as a means to reduce their own's food insecurity, which is also key development challenges in Bangladesh. However, little empirical research has conducted on this issue, especially in the rural area of Bangladesh. Therefore, the present study was conducted to examine the relationship of six domains of women's empowerment with their food security in rural Bangladesh using a partial least square structural equation modelling approach. Our empirical analysis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 97 publications
0
18
0
Order By: Relevance
“…Achieving gender equality is regarded as one of the key goals of the 2030 Agenda for Sustainable Development, as women and girls continue to suffer serious discrimination problems in every part of the world [ 1 ]. The vital aspect of the goal of women’s empowerment is connected to improving health and nutrition status, ensuring food security, eliminating hunger, and reducing poverty [ 2 , 3 ]. “Poverty is a pronounced deprivation of well-being”, whereas well-being is measured by education, assets, housing, health, nutrition, and certain human rights in society [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Achieving gender equality is regarded as one of the key goals of the 2030 Agenda for Sustainable Development, as women and girls continue to suffer serious discrimination problems in every part of the world [ 1 ]. The vital aspect of the goal of women’s empowerment is connected to improving health and nutrition status, ensuring food security, eliminating hunger, and reducing poverty [ 2 , 3 ]. “Poverty is a pronounced deprivation of well-being”, whereas well-being is measured by education, assets, housing, health, nutrition, and certain human rights in society [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…To elaborate, in studying the association between the indicators of empowerment and food security, findings often indicate trade‐offs (Aziz et al, 2020; Wei et al, 2021); that is, empowerment does not necessarily affect food security, or other nutrition outcomes, positively for women (Cornwall, 2016; Essilfie et al, 2021; Quisumbing et al, 2021; Tsiboe et al, 2018). This outcome is likely because existing indices do not account for nutrition‐sensitive indicators in operationalizing empowerment, and their focus is mainly on economic enablers and productive resources while targeting a nutrition or food security outcome.…”
Section: Introductionmentioning
confidence: 99%
“…The study found that female-headed households are less food secure compared to male-headed households after controlling for both observed and unobserved factors. There are also strands of studies that have examined the effects of women's empowerment on food security [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%